Simulação e análise de redes de sensores sem fio aplicadas à viticultura - Verona, André Barbosa (2010)
Agriculture is one of the most important economic activities in Brazil. However, this activity is submitted to a direct influence of weather conditions. Adverse climatic conditions can cause enormous economic losses and serious social and environmental impacts. On this context, it came to us the challenge to predict and control such adverse conditions. The effort therein consists in employing the science of meteorology focused on a support for agriculture (Agrometeorology). The agrometeorological microstation emerged for this purpose, and are able to collect and store weather data like temperature and humidity. They, however, collect data that reflect the microclimate of a small area, requiring the use of several of them to monitor large areas. Lacking ability to communicate with each other, the data collection demand extra effort with human material. An interesting option that has recently emerged are the networks of wireless sensor network (WSN), which consist of devices capable of sensing the environment and can communicate with each other, sending the collected data across all devices to a collection point centralized. In this study, several configurations of WSN were simulated and analyzed, in order to identify what are the configuration parameters with best performance, considering the time of life, delay in delivery and data loss for WSNs, applied in the monitoring of grape plantations. Thus, it was possible to reach a lot of farmers in the town of Marialva - PR, a city that stands out for its large production of grapes, moving the economy of the city and the region. Also a further study was carried out upon the vine culture to identify major climatic factors that influence them, using it as parameters in the simulations. As an end result of this study, it was found the best routing protocol, the best location of the AP (Access Point) and the best organization of the network using the characteristics of the Mica2 sensor node, which can be used as a guide for the deployment of a real WSN for monitoring of climate on grape crops, to increase the life span, reduce the delay in delivery of data and reduce the number of missing data in the network.